Silica Waste Utilization in Ground Improvement: A Study of Expansive soil Treated with LRHA - Agus Setyo Muntohar, Roslan Hashim (2002)
soil is a problem in Indonesia such as in other countries. Current research found that there is a potential of using silica waste was resulting from the burning of rice husk as a pozzolanic materials. This paper presents the results of study on the silica waste utilization produced from open field rice husk burnt in Yogyakarta (Indonesia). The rice husk ash and lime was mixed to stabilise expansive soils. In this research, a series of laboratory tests has been conducted namely the physical and index properties, compaction, CBR, consolidation, and shear strength tests. The research shows that lime – rice husk ash decreased the swell of expansive soil and improved its strength and bearing capacity. It implies that the agricultural waste can be turned into a practical use.